Effects of Radiation on Materials: 20th International Symposium 2001
DOI: 10.1520/stp10534s
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Through-Thickness Changes in Primary Damage Production in Commercial Reactor Pressure Vessels

Abstract: An extensive database of atomic displacement cascades in iron has been developed using the method of molecular dynamics (MD). More than 300 simulations have been completed at 100K with energies between 0.1 and 100 keV. This encompasses nearly all energies relevant to fission reactor irradiation environments since a 100 keV MD cascade corresponds to the average iron cascade following a collision with a 5.1 MeV neutron. Extensive statistical analysis of the database has determined representative average values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Reliability of such estimations has been examined using irradiation defect production calculations and mechanical property tests on decommissioned pressure vessels [139]. For example, molecular dynamics calculations of freely migrating point defects with a neutron transport calculation through pressure vessel steels revealed that the dpa attenuation trend was suitable to predict the attenuation of damage production [140]. Data from the decommissioned French PWR Chooz A pressure vessel demonstrated that the change in measured transition temperature shift was in agreement with the trend of the predicted shift assuming a dependence of (fluence) 0.48 [141].…”
Section: Attenuation Through the Pressure Vessel Wallmentioning
confidence: 99%
“…Reliability of such estimations has been examined using irradiation defect production calculations and mechanical property tests on decommissioned pressure vessels [139]. For example, molecular dynamics calculations of freely migrating point defects with a neutron transport calculation through pressure vessel steels revealed that the dpa attenuation trend was suitable to predict the attenuation of damage production [140]. Data from the decommissioned French PWR Chooz A pressure vessel demonstrated that the change in measured transition temperature shift was in agreement with the trend of the predicted shift assuming a dependence of (fluence) 0.48 [141].…”
Section: Attenuation Through the Pressure Vessel Wallmentioning
confidence: 99%
“…• a 'short-term irradiation' module treats the neutron spectrum to provide the PKA spectrum (with the code SPECMIN 4 [27,28]). Then, using this spectrum as source term, INCAS gives the induced sub-cascade spectrum (number of sub-cascades versus their dissipated energy).…”
Section: Hfir Sub-cascade Spectrummentioning
confidence: 99%
“…( 2) obtained from the least square fitting is numerically different from the value of Σ '() in Eq. (1). Therefore, the difference between the fittings from Eqs.…”
Section: Attenuation Of Dpamentioning
confidence: 98%
“…However, Refs. [1], [3] show that the attenuation of DPA is different from the recommended formula of the US Nuclear Regulatory Commission (NRC) regulatory guide 1.99 revision 2 [8], based on neutron fluence above 1 MeV [8]. Our recent work [5] points out that the neutron fluence above 0.5 MeV is quite representative of DPA in the SS heavy reflector from the point of view of attenuation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation